Magical realism in the novels of Jeanette Winterson - Dvořáčková, Lenka (2006)
In my diploma thesis I provide an analysis of the magical realist aspect in the novels of Jeanette Winterson (1959- ), one of the most influential and renowned representatives of the contemporary British literary scene. On the analysis of three of her novels \x{2013} The Passion (1987), Sexing the Cherry (1989) and Gut Symmetries (1997) \x{2013} and their comparison with the works of renown magical realist authors - Gabriel García Márquez ( One Hundred Years of Solitude -1967), Salman Rushdie (Midnights Children - 1978; The Satanic Verses - 1989) and Angela Carter ( Nights in the Circus - 1984), I wanted to prove that the novelist can be ragarded, to a certain degree, a magical realist writer. Wintersons prose is too varied to be typecast as a pure magical realist prose, however, her literary work encompasses many charactersitic features of magical realism